The collection of Lithuanian books in the British library (continuation) - Aušra Navickienė; Janet Zmrozek (Knygotyra)
Lithuanian books are part of the broader collection of books in Slavonic and other languages of Eastern Europe at the British Library. In this article, the authors present the results of the latest investigation of the collection, which contains unique copies of books very important for Lithuanian culture. The aim of the investigation was to examine Lithuanian books published between 1547 and 1904 and to clarify the history of this collection. In total, 229 copies of Lithuanian printings and 23 old Lithuanian texts in foreign language books have been identified. During the investigation, data about each book were gathered and analyzed. The studied books are presented in an alphabetical list.